2006
DOI: 10.1038/sj.cdd.4401932
|View full text |Cite
|
Sign up to set email alerts
|

Role of geminin: from normal control of DNA replication to cancer formation and progression?

Abstract: The normal cell proliferation involves the passage through a series of finely regulated phases that are known as cell cycle checkpoints. In order to carry out a correct replication, the eukaryotic cell undergoes to a series of events ensuring that each copy of duplicated chromosome exactly segregates in each of daughter cells. 1,2 A main critical control of the cell cycle is to ensure that the DNA replication takes place and that it is followed by mitosis, once for each cell cycle. Alterations in the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 60 publications
0
12
0
2
Order By: Relevance
“…However, the effect of altering the GMNN/CDT1 balance in tumourigenic cells (which express higher levels of these genes compared to normal cells [31]) is unclear as there is debate about how the GMNN/CDT1 balance influences the development and progression of cancer [26,27,28,39,40]. Additionally we have also shown that the expression of MCM2 and MCM7 is reduced by ENL in the prostate cell lines used, and this may be linked altered CDT1 expression as CDT1 is required for the loading of the MCM complex during the initiation of DNA replication [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of altering the GMNN/CDT1 balance in tumourigenic cells (which express higher levels of these genes compared to normal cells [31]) is unclear as there is debate about how the GMNN/CDT1 balance influences the development and progression of cancer [26,27,28,39,40]. Additionally we have also shown that the expression of MCM2 and MCM7 is reduced by ENL in the prostate cell lines used, and this may be linked altered CDT1 expression as CDT1 is required for the loading of the MCM complex during the initiation of DNA replication [24].…”
Section: Discussionmentioning
confidence: 99%
“…The loading of this MCM complex is facilitated, in part, by chromatin licensing and DNA replication factor 1 (CDT1), which is itself negatively regulated by geminin (GMMN). Abnormal expression of GMNN, CDT1, and MCM2 and 7 have been linked with the malignant progression of prostate cancer [25,26,27,28,29,30,31]. Another key signalling pathway disrupted in prostate cancer is the phosphoinositide-3-kinase (PI3K)-AKT signalling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, accurate control of the balance between Cdt1 and geminin is essential for cell survival and genetic stability. Using gene expression profiling in cancer diagnostics, Cdt1 and geminin have become important targets (for a review, see Montanari et al , 2006). We suggest that the evaluation of their ratio might be as important to predict clinical outcome as the simple evaluation of their absolute levels.…”
Section: Discussionmentioning
confidence: 99%
“…These phenotypes were relatively well associated with the histologically poor degree of tumor differentiation and tumor local invasiveness. Geminin, which is also one of the DNA replication licensing factors, is expressed during the S, G2, and M phases but not in G0 and G1 phases, and is degraded at M phase without playing a specific role in cell division control (36). It has been suggested that Geminin might provide useful information about tumor proliferation activities that is equal or superior to that of MCM proteins or Ki-67.…”
Section: Discussionmentioning
confidence: 99%